2020
DOI: 10.1002/ptr.6636
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin‐induced normal breast epithelial cellular aging and its related breast cancer growth through mitochondrial autophagy and oxidative stress mitigated by ginsenoside Rh2

Abstract: Clinical dose of doxorubicin (100 nM) induced cellular senescence and various secretory phenotypes in breast cancer and normal epithelial cells. Herein, we reported the detailed mechanism underlying ginsenoside Rh2‐mediated NF‐κB inhibition, and mitophagy promotion were evaluated by antibody array assay, western blotting analysis, and immunocytostaining. Ginsenoside Rh2 suppressed the protein levels of TRAF6, p62, phosphorylated IKK, and IκB, which consequently inactivated NF‐κB activity. Rh2‐mediated secretor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…20( R )-Rg3 reduced MDA levels and increased SOD and CAT production through a mechanism related to inhibition of the MAPK/NF- κ B signaling pathway. Hou et al [ 109 ] studied the effects of ginsenoside Rh2 on adriamycin-induced cell senescence in breast cancer and normal epithelial cells and confirmed that ginsenoside Rh2 reduced ROS production, increased SOD expression, reduced oxidative stress, and inhibited the NF- κ B signaling pathway in senescent cells. Chen et al [ 107 ] found that ginsenoside Rg3 can reduce TNF- α -induced damage to human NPCs by blocking the NF- κ B signaling pathway.…”
Section: Roles Of Ginsenosides and Different Signaling Pathways In Th...mentioning
confidence: 99%
“…20( R )-Rg3 reduced MDA levels and increased SOD and CAT production through a mechanism related to inhibition of the MAPK/NF- κ B signaling pathway. Hou et al [ 109 ] studied the effects of ginsenoside Rh2 on adriamycin-induced cell senescence in breast cancer and normal epithelial cells and confirmed that ginsenoside Rh2 reduced ROS production, increased SOD expression, reduced oxidative stress, and inhibited the NF- κ B signaling pathway in senescent cells. Chen et al [ 107 ] found that ginsenoside Rg3 can reduce TNF- α -induced damage to human NPCs by blocking the NF- κ B signaling pathway.…”
Section: Roles Of Ginsenosides and Different Signaling Pathways In Th...mentioning
confidence: 99%
“…Ginsenoside, a potential treatment candidate for the attenuation of aging-related disease [87], produces antidepressant-like effects on chronic unpredictable mild stress-exposed rats involving protection against oxidative stress and thus the neuronal deterioration resulting from inflammatory responses [88]. Ginsenoside not only upregulates GPX4 to reduce oxidative stress and thereby alleviates 6-hydroxydopamine-induced neuronal damage [89] but also effectively attenuates D-galactose-induced oxidative stress via restoring the upstream PI3K/AKT signaling pathway [90].…”
Section: Tcm-based Bioactive Compounds Andmentioning
confidence: 99%
“…However, the emergence of resistance has limited the potential of chemotherapy. Doxorubicin (DOX) is one of the effective chemotherapeutic compounds that restricts cancer proliferation by inhibiting microtubule disassembly (Hou, Yun, Xue, Jeon, & Kim, 2020). This agent is extensively applied in treatment of lung cancer (E. S. Lee et al, 2020).…”
Section: Curcumin and Lung Cancermentioning
confidence: 99%